Measuring Students’ Ability in Using Collocations in Argumentative Writing Across Gender - Annike Putri Ardi (English Department FBS UNP, 2022)
This research is a descriptive study. It investigates the difference of EFL male and female students’ ability in using collocations in argumentative writing. There were 24 students taking a writing test in this research. They were 17 female and 7 male students. The test used a writing test with two different writing prompts to be chosen by the students. The rubric focused on the use of collocationsas other elements of writing are ignored to make the test valid. The research findings show that overall score of the students’ ability in using collocations in argumentative writing is 63.8 which is in average level. There is no student with excellent ability, 13 students with good ability, 7 students with average ability, 3 students with fair ability and 1 student with poor ability. Another finding, even with different score 64.2 for male and 62.7 for female, there is no difference between the male and female students’ ability in collocations in argumentative writing as they both are in average level. In conlusion, the ability in using collocations of male and female students is in the same level.